2015
DOI: 10.1002/2015gl064842
|View full text |Cite
|
Sign up to set email alerts
|

On the lognormality of historical magnetic storm intensity statistics: Implications for extreme‐event probabilities

Abstract: An examination is made of the hypothesis that the statistics of magnetic storm maximum intensities are the realization of a lognormal stochastic process. Weighted least squares and maximum likelihood methods are used to fit lognormal functions to −Dst storm time maxima for years 1957–2012; bootstrap analysis is used to established confidence limits on forecasts. Both methods provide fits that are reasonably consistent with the data; both methods also provide fits that are superior to those that can be made wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
112
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(120 citation statements)
references
References 52 publications
3
112
2
Order By: Relevance
“…A common approach is to use long geomagnetic data sets to extrapolate indices (Siscoe, 1976;Love et al, 2015;Riley, 2012), or to extrapolate the amplitude of the variation field or its time derivative (Danskin & Lotz, 2015;Love et al, 2016;Thomson et al, 2011). A related possibility is to extrapolate the geoelectric field modelled from magnetic field data (Myllys et al, 2014;Nikitina et al, 2016;Pulkkinen et al, 2012;2015;Wintoft et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A common approach is to use long geomagnetic data sets to extrapolate indices (Siscoe, 1976;Love et al, 2015;Riley, 2012), or to extrapolate the amplitude of the variation field or its time derivative (Danskin & Lotz, 2015;Love et al, 2016;Thomson et al, 2011). A related possibility is to extrapolate the geoelectric field modelled from magnetic field data (Myllys et al, 2014;Nikitina et al, 2016;Pulkkinen et al, 2012;2015;Wintoft et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Riley [2012] chose x min = 120, while Love et al [2015] used x min = 63 as a lower bound for |Dst|. Here we use an approach for optimizing the value of x min based on minimizing the Kolmogorov-Smirnov (KS) goodness-of-fit statistic between the model and the data [Clauset et al, 2009].…”
Section: Identifying the Tail In The Distributionmentioning
confidence: 99%
“…Riley [2012] and Love et al [2015] identified the minimum values in severity (x min ) manually and, arguably, somewhat subjectively. In particular, Riley [2012] chose x min = 120, while Love et al [2015] used x min = 63 as a lower bound for |Dst|.…”
Section: Identifying the Tail In The Distributionmentioning
confidence: 99%
See 2 more Smart Citations